Introduction of oxygen vacancy to manganese ferrite by Co substitution for enhanced peracetic acid activation and 1O2 dominated tetracycline hydrochloride degradation under microwave irradiation. (15th October 2022) - Li, Shuo; Yang, Yalun; Zheng, Heshan; Zheng, Yongjie; He, Chuan-Shu; Lai, Bo; Ma, Jun; Nan, Jun
Highlights: Modified MFO was firstly used for microwave-activated PAA degradation of TCH. Cobalt substitution produced OVs and improved the MW absorbing properties. 1 O2 played a dominant role in TCH degradation. Both formed OVs and microwave contributed to the generation of 1 O2 . The degradation intermediates of TCH were successfully detoxified. Abstract: High microwave-response cobalt-substituted manganese ferrite (CMFO-0.5) was successfully synthesized as a heterogeneous catalyst for efficient peracetic acid (PAA) activation and tetracycline hydrochloride (TCH) degradation with singlet oxygen ( 1 O2 ) as the dominated reactive oxidized species (ROS). The removal efficiency of TCH could reach 98.16% within 6 min under microwave irradiation when the CMFO-0.5 was added at 20 mg/L. It's found that the Co substitution could produce the oxygen vacancies (OVs), improve the microwave (MW) absorbing performance and enhance the internal electron transfer efficiency of materials. The phenomenon why 1 O2 as the dominated ROS rather than hydroxyl radical (OH) and organic radicals (R-O) would be explained by the following aspects: the oxygen adsorbed on the OVs can accept the electron transformed from PAA to form superoxide radical (O2 − ), which will disproportionate to form 1 O2 ; the energy generated by the non-thermal effect of MW can dissociate PAA to generate peroxy-group for 1 O2 generation. Furthermore, the possible TCH degradation pathways were proposed based on DFT theory calculations and product identification, and the toxicity predictions of the degradation products were also performed by the Ecological Structure-Activity Relationship Model (ECOSAR) software. Additionally, the decrease of acute toxicity of treated TCH, excellent stability and strong resistance towards water matrix fully demonstrate the superiority of the proposed system for practical application in wastewater treatment. Graphical abstract: Image, graphical abstract